2014
DOI: 10.1016/j.jval.2014.03.1322
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden Of Psoriatic Patients In The Brazilian Health System

Abstract: MCO) due to the severity of the conditions and their minimal budet impact. However, as interest by pharmaceutical companies, competition, and spend in the orphan drug category grows, payers are likely to look for ways to reduce or contain the cost. This is particularly true among pharmacy benefit products where payers have more effective utilization management tools at their disposal when compared to medical benefit products. Methods: This research assessed the Wholesale Acquisition Cost (WAC) of all non-onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Contrary to most studies published in other regions, 64 , 65 , 66 , 67 , 68 Latin American literature did not find a statistically significant difference in work productivity across levels of Pso severity. 15 , 31 This discrepancy, however, may be attributed to the small sample sizes of these studies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Contrary to most studies published in other regions, 64 , 65 , 66 , 67 , 68 Latin American literature did not find a statistically significant difference in work productivity across levels of Pso severity. 15 , 31 This discrepancy, however, may be attributed to the small sample sizes of these studies.…”
Section: Discussionmentioning
confidence: 84%
“…In contrast, Ferreira et al found no significant differences in absenteeism, presenteeism, overall work impairment, and activity impairment across varying levels of Pso severity. 31 …”
Section: Resultsmentioning
confidence: 99%